Reliability of OMERACT Scoring System in Ultra-High Frequency Ultrasonography of Minor Salivary Glands: Inter-Rater Agreement Study - Rossana Izzetti; Giovanni Fulvio; Marco Nisi; Stefano Gennai; Filippo Graziani (Journal of Imaging, 2022)
Minor salivary gland ultra-high frequency ultrasonography (UHFUS) has recently been introduced for the evaluation of patients with suspected primary Sjögren’s Syndrome (pSS). At present, ultrasonographic assessment of major salivary glands is performed using the Outcome Measures in Rheumatology (OMERACT) scoring system. Previous reports have explored the possibility of applying the OMERACT scoring system to minor salivary glands UHFUS, with promising results. The aim of this study was to test the inter-reader concordance in the assignment of the OMERACT score to minor salivary gland UHFUS. The study was conducted on 170 minor salivary glands UHFUS scans of patients with suspected pSS. Three independent readers performed UHFUS image evaluation. Intraclass correlation coefficient (ICC) was employed to assess inter-reader reliability. Bland and Altman analysis was employed to test the agreement with a gold standard examiner. ICC values > 0.9 were found for scores 0 and 1, while score 2 and score 3 presented ICCs of 0.873 and 0.785, respectively. The measurements performed by the three examiners were in agreement with the gold standard examiner. According to these results, UHFUS interpretation showed good inter-observer reliability, suggesting that OMERACT score can be effectively used for the evaluation of glandular alterations, even for minor salivary glands.